Safety and Health of Employees in the Blame Culture - Chomątowska, Barbara (Acta Universitatis Lodziensis. Folia Oeconomica, 2013)
Competitiveness of modern organisations depends on competent, motivated and healthy employees. Enterprises more and more often focus on the improvement of the occupational health and safety. It is not only caused by legal or social reasons. The management teams start to understand that they may derive benefits from investment in the occupational health and safety, from proper management of this area. An important factor deciding on the efficiency and effectiveness of the OHS management is the safety culture. The purpose of this article is to describe the subject matter of the safety culture of an enterprise, its essence, importance for an effective OHS management. Author of this elaboration presents how difficult it is to realize the aim of improvement of the OHS condition in work places with poor, low safety culture, especially in the blame culture. The article was prepared by studying the national and foreign literature of the subject and interviews which the author conducted with the representatives of economic practice.